7.6k views
7 votes
Equation for geometric sequence 6,12,24,48,96

2 Answers

8 votes


This is a geometric sequence since there is a common ratio between each term. In this case, multiplying the previous term in the sequence by
2
2
gives the next term. In other words,
a
n
=
a
1

r
n

1
a
n
=
a
1

r
n
-
1
.
Geometric Sequence:
r
=
2
r
=
2
This is the form of a geometric sequence.
a
n
=
a
1
r
n

1
a
n
=
a
1
r
n
-
1
Substitute in the values of
a
1
=
6
a
1
=
6
and
r
=
2
r
=
2
.
a
n
=
(
6
)

(
2
)
n

1
a
n
=
(
6
)

(
2
)
n
-
1
Remove parentheses.
a
n
=
6

2
n

1
User Zhong Huiwen
by
5.4k points
8 votes

Answer:

a(n)=6*2^(n-1)

Explanation:

a(n)=a(1)r^(n-1)

a(1) = 6

a(2)=6r^1=12

r=2

a(n)=6*2^(n-1)

User Dionne
by
5.3k points